Tingkat Korelasi Prestasi Akademik terhadap Siswa SMP Menggunakan Metode Backpropagation - Yeni, Nasma; Yunus, Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2021)
Student academic achievement plays an important role in determining the quality of a school. Student scores sometimes change each semester, there are increases and decreases. There is an assumption that students who scored well in the previous semester will be good in the next semester and vice versa. This method is expected to make it easier for educators to see the extent of changes in student academic achievement. The data tested were data from 60 grade VII students in 2 semesters. Furthermore, it will be tested using the MatLab application, then the results of the changes that will occur will appear. The results of this study found that the correlation between semester 1 scores and semester 2 TP scores. 2019/2020 is very good with an architectural pattern of 10-10-1 with an accuracy value of 95.3%. So students who excel in semester 1 are likely to excel in the next semester, so that they can help the school see the Correlation Level of Student Academic Achievement at SMPN 3 Lengayang.